THE MEANING OF LIFE AND THE DYNAMICS OF VALUES WITHIN THE FRAMEWORK OF ANTHROPIC THEORY (World Bulletin of Social Sciences, 2025)
The main problem of modern anthropogenic impact, from the perspective of humanity’s limitless needs and the limited possibilities of nature, requires cosmology—as a component of the philosophical worldview—to undergo epistemological analysis of certain conceptual and methodological processes that arise in the cosmos. In particular, discoveries made in recent years call for new scientific interpretations and ways of thinking. One such approach, which explains the universe and humanity’s place within it, is the “anthropic principle,” which plays an important role.